Cardiovascular and ocular safety of α1-adrenoceptor antagonists in the treatment of male lower urinary tract symptoms. (September 2014) - Oelke, Matthias; Gericke, Adrian; Michel, Martin C
<x xml:space="preserve">Abstract</x> Introduction: α1-Adrenoceptor antagonists (α-blockers) represent first-line drug treatment for male lower urinary tract symptoms. Their adverse events (AEs) include asthenia, dizziness, nasal congestion, arterial (orthostatic) hypotension and intraoperative floppy iris syndrome (IFIS). Areas covered: This report focuses on cardiovascular and ocular AEs of α-blockers as related to their mechanism of action and subtype selectivity. Expert opinion: The incidence of hypotension differs between α-blockers. It is greatest with doxazosin or terazosin, but others including tamsulosin can also lead to hypotension especially upon treatment initiation. Concomitant antihypertensive medication increases the incidence of hypotension with some α-blockers. Use of α1A-selective blockers, evening dosing and drug intake after a meal can reduce the risk of hypotension. IFIS can occur with all drugs exerting α1-adrenoceptor antagonist properties and has especially been reported for tamsulosin. It makes cataract surgery more challenging but does not constitute a health risk to patients. IFIS seems to result from inhibition of iris dilator muscle contraction and occurs in men or women, even after α-blockers have been discontinued. To reduce the risk of IFIS, the authors suggest taking a careful drug history, postponing α-blocker treatment for patients with scheduled cataract surgery and careful counseling of patients taking α-blockers.